Melt-processing of sbs/polyaniline-based blends (2013)
Morphological analysis and electrical conductivity of composites obtained by melt-processing of blends of a polyaniline complex (PANICX) with styrene-butadiene-styrene (SBS) are reported. Blends with PANICX contents ranging from 1 to 50 wt% were first prepared using a two-piece batch mixer, followed by ram-extrusion to obtain cord-like extrudates. The microstructure was analyzed by SEM, and conductivity was evaluated with a Keithley electrometer. The blends’ rheological behavior was also studied. Evidence of formation of well-defined elongated structures was found in most of the extrudates. The extrudates’ conductivity was considerably low. Inhomogeneity-related problems were observed such as erratic behavior of pressure, “melt-fracture” during the extrusion, and extrudates with irregular microstructure and very low conductivity. This occurred because same size batches were used regardless of blends’ composition. As a result, the shearing occurring during compounding was not enough to disperse PANICX effectively within the SBS matrix.